The Understanding of Culturally Responsive Pedagogy Among High School Students and Teachers in East Kalimantan - Susilo Susilo; I Gusti Ngurah Darmawan; Dyah Sungginwati; Syaiful Arifin; Khairun Nisyah; Rinda Cahya Mudiawati (Journal of Innovation in Educational and Cultural Research, 2025)
This study aims to assess the knowledge of culturally responsive education among high school teachers and students in East Kalimantan, Indonesia. It utilizes a mixed-methods design, adopting a convergent mixed-methods approach. Data for this research were collected from high school students across various districts and cities within the province of East Kalimantan. The research data comprise quantitative information from questionnaire responses regarding knowledge of culturally responsive education. A questionnaire, commonly employed in survey research, is a structured instrument in which student participants select answers to pre-designed questions and provide basic demographic or personal information. Qualitative data were gathered through in-depth interviews with teachers. Data analysis involves two approaches: qualitative and quantitative. The qualitative analysis uses NVIVO software, while the quantitative analysis employs descriptive statistics and inferential t-tests. The findings indicate that all respondents fall within the proficient classification. The interviews with three teachers reveal four themes: 1) awareness and understanding of cultural diversity, 2) addressing injustice in the classroom, 3) building cross-cultural communication, and 4) curriculum and cultural diversity.